Impact of b‐value on estimates of apparent fibre density. Issue 10 (26th March 2020) - Genc, Sila; Tax, Chantal M. W.; Raven, Erika P.; Chamberland, Maxime; Parker, Greg D.; Jones, Derek K.
Abstract: Recent advances in diffusion magnetic resonance imaging (dMRI) analysis techniques have improved our understanding of fibre‐specific variations in white matter microstructure. Increasingly, studies are adopting multi‐shell dMRI acquisitions to improve the robustness of dMRI‐based inferences. However, the impact of b ‐value choice on the estimation of dMRI measures such as apparent fibre density (AFD) derived from spherical deconvolution is not known. Here, we investigate the impact of b ‐value sampling scheme on estimates of AFD. First, we performed simulations to assess the correspondence between AFD and simulated intra‐axonal signal fraction across multiple b ‐value sampling schemes. We then studied the impact of sampling scheme on the relationship between AFD and age in a developmental population ( n = 78) aged 8–18 (mean = 12.4, SD = 2.9 years) using hierarchical clustering and whole brain fixel‐based analyses. Multi‐shell dMRI data were collected at 3.0T using ultra‐strong gradients (300 mT/m), using 6 diffusion‐weighted shells ranging from b = 0 to 6, 000 s/mm 2 . Simulations revealed that the correspondence between estimated AFD and simulated intra‐axonal signal fraction was improved with high b ‐value shells due to increased suppression of the extra‐axonal signal. These results were supported by in vivo data, as sensitivity to developmental age‐relationships was improved with increasing b ‐value ( b = 6, 000 s/mm 2, median R 2 = .34; b = 4, 000 s/mm 2, median R 2 = .29; b = 2, 400 s/mm 2, median R 2 = .21; b = 1, 200 s/mm 2, median R 2 = .17) in a tract‐specific fashion. Overall, estimates of AFD and age‐related microstructural development were better characterised at high diffusion‐weightings due to improved correspondence with intra‐axonal properties.